Association between neotropical burrowing spiders (araneae: nemesiidae) and mites (acari: heterostigmata, scutacaridae) - Ebermann, Ernst (2002)
Whilst collecting burrowing spiders of the family Nemesiidae from 16 localities in Argentina, phoretic mites were found on Stenoterommata iguazu, Stenoterommata platense and Stenoterommata uruguai. These mites are described here: Scutacarus (S.) araneophilus n. sp. and Scutacarus (S.) adgregatus n. sp. Assocations between spiders and scutacarids were not previouly known. Aspects of the biology of the spiders and the interactions between mites and spiders are reported and discussed.